Histopathological findings of clinically diagnosed migratory testis - Kohdaira, T (Hinyokika kiyo. Acta urologica Japonica, 1985)
Clinically diagnosed migratory testis in patients 3-years old and over were histopathologically evaluated. Before the pubertal age, seminiferous tubules were histologically within normal, partially immature, but after the pubertal age they were degenerative as cryptorchid. It was pointed out that degenerative changes could occur in seminiferous tubules if orchiopexy is not performed before the prepubertal stage